Tinjauan pengenaan pajak penghasilan peserta pendidikan dan pelatihan pada PT Bank Sulselbar Cabang Utama Makassar - Anisa Azzahra; Sri Nirmala Sari; Ilham Ilham (Income Journal: Accounting, Management and Economic Research, 2022)
Tax is one of the biggest contributions in state cash receipts. Article 23 income tax (PPh) is a tax on income by name and in any form derived from capital, delivery of services, or implementation of activities other than those that have been deducted by Article 21 of Income Tax.The purpose of this research was to find out, article 23 tax payments and reporting for training services and / or at PT Bank Sulselbar Makassar Main Branch with compliance with the Taxation Law No. 36 of 2008 and PMK NO. 141 / PMK.03 / 2015. The research method used is qualitative, data and secondary sources, procedures for data retrieval by conducting interviews, data analysis techniques are data analysis of Milles and Huberman models that are carried out interactively and continue until the completion of the data is saturated. The results of the sresearch show that PT Bank Sulselbar Makassar Main Branch carries out the work of cutting, depositing and reporting Article 23 of Income Tax not in accordance with the Director General of Taxation, Depositing and Reporting / or Income Tax Article 26 Work with Work, Services, and Personal Activities CHAPTER III Article 3 Letter f Point 4, the recipient who is withheld PPh Article 21 and / or PPh Post 26 is the income of the participant in education and training. Individual administration for companies as withholding to improve compliance.